15-Minute City Models: Justice, Mobility, and Land-Use in Cairo - Cherif, Reem (Trinity College Dublin. School of Natural Sciences. Discipline of Geography, 2026)
This thesis examines the 15-Minute City concept as both a global paradigm and a locally situated urban practice, using Greater Cairo and three of its historically distinct urban areas as a lens. While the concept, built on principles of proximity, density, diversity, and digitalisation, has become central to debates on sustainability and mobility in post-pandemic cities, its understanding remains predominantly shaped by European perspectives. Through a comparative analysis of Agouza, Madinaty, and Badya (under construction), the study explores how governance trajectories, planning and design logics, and lived experiences shape different 15-minute city models, whether existing or planned from scratch. This builds on the 15-minute city concept lineage of urban ideals: The Garden City Concept and New Urbanism. It illustrates how urban form, mobility patterns, and digital infrastructures intersect with residents' daily practices and social ties, shaping their experiences of accessibility and belonging. The research is based on a comparative mixed-methods case-study approach that combines spatial analysis with qualitative inquiry. Spatially, it employs service area analysis (CLFS framework and service area coverage maps) to examine the manifestations of proximity, density, and diversity in Agouza, Madinaty, and Badya. Typological and morphological readings (MTSC framework) of buildings and neighbourhood form are concluded to understand how design choices shape the patterns. The study relies on semi-structured multi-stakeholder interviews with residents, government representatives, and industry representatives. These interviews were thematically analysed to capture lived experiences of access to services, mobility, and community life, as well as the growing role of digital platforms in mediating access. This integration allows the research to move beyond abstract urban ideals, grounding the analysis in both measurable patterns of urban form and movement and in residents' lived realities and meanings. Examining the three case studies, several themes emerged related to the different 15-minute city models. For residents, the accessibility to services feels reliable when diversity is paired with redundancy, that is, when there is more than one realistic option for essential services. In large parts of Madinaty and Badya, many district interiors feel more single-option, with services concentrated in one main cluster. In Madinaty, these commercial clusters reflect a New Urbanist planning logic, while in Badya they reflect a more hierarchical 15-minute city approach. In both cases, residents experiences reveal the limits of this arrangement: when a key facility is closed, overcrowded, or too expensive, proximity becomes fragile, what is nearby in principle quickly turns into a detour in practice. Agouza, by contrast, shows a layered, locally adapted Garden City fabric that has built up over time. Most services have accumulated multiple nearby alternatives, which strengthens everyday resilience. However, this redundancy of services also brings consequences, including pressure on streets and sidewalks, more traffic and noise, and ongoing parking stress. Second, mobility mode is a key factor. Cycling consistently acts as the equaliser, dramatically expanding what is reachable in the suburban cases and reducing edge distances in Agouza, often more than any planned proximity. However, in practice, people switch away from cars only when cycling routes are comfortable and safe door-to-door: softened edges (shade, crossings), protected cycle links, and end-of-trip support. Without these settings, walking and cycling remain recreational. Third, activity nodes, community and social circles are the anchors that shape everyday life. Frequent local nodes in Agouza make walking functional and social ties locally resilient. In Madinaty and Badya, social life is more limited and channelled into a few planned nodes, making everyday social encounters less frequent and less layered. Centralised planned nodes in Madinaty concentrate on leisure. Provisional nodes in Badya can seed early routines, but until the fabric matures, they dont hold social life within a 15-minute radius. Fourth, the study shows that digital platforms have become an invisible infrastructure of proximity. They complement the strong urban form in Agouza and reduce deficits in the new towns, effectively stretching or reshaping the lived 15-minute radius through delivery. This can reduce unnecessary short car trips, but it can also reinforce car-first routines unless neighbourhood pick-up nodes are designed to turn digital convenience into active trips. From a broader perspective, conceptually, the research widens debates on the 15-minute city concept by positioning Cairo as an active site of urban knowledge. Methodologically, it develops and applies an integrated comparative mixed-methods framework that triangulates spatial quantitative metrics (service area analysis and CLFS framework), with qualitative inquiry (interviews, field notes, and thematic coding), thick mapping and morphological analysis (MTSC framework). This enables understanding and evaluation of context-specific 15-minute city models, examining how urban form becomes lived 15-minute-radius accessibility. Practically, it draws attention to both the possibilities and the constraints of applying 15-minute city principles in fast-urbanising contexts such as Greater Cairo. In conclusion, the thesis shows that the 15-minute city is not a single formula but a plurality of models shaped by history, governance, and lived experience. It offers critical reflections on urban theory while providing planners and designers with grounded insights into how cities might move toward more just and inclusive forms of proximity planning.
APPROVED
Keywords: Proximity Planning; Sustainable Urbanism; Global Urbanism; Mixed-use development; Compact City; 15-minute city; Metropolitan Area